Service virtualization : reality is overrated - Michelsen, John (CA Technologies Press, 2012)
Writing for executive and technical readers alike, the authors capture lessons learned from the first five years of applying this game-changing practice in real customer environments. Other industries, from aviation to medicine, already understand the power of simulation to solve real-world constraints and deliver new products to market better, faster, and cheaper. This book discusses why, when, where, and how to deploy service virtualization (SV) solutions to mitigate or eliminate the constraints of an unavailable or unready service system by simulating its dependent components in order to deliver better enterprise software faster and at lower cost. In particular, it covers deploying SV solutions including shift-left, infrastructure availability, performance readiness and test scenario management. This book is not only for IT practitioners on engineering, testing, and environments teams engaged in the development and delivery of enterprise software, but also for executives of companies in all sectors who need to understand and implement emergent opportunities to improve the time to market and overall competitiveness of any outward-facing business strategy that has a software application component.